Pengaruh Jangka Waktu, Jaminan Kredit, Tingkat Suku Bunga, dan Karakter Para Debitur Terhadap Besarnya Kredit Macet Pada Lembaga Perkreditan Desa (LPD) di Desa Pekraman Sanur, Kecamatan Denpasar Selatan - Made Egar Dirotsaha Putra; Sri Eka Jayanti; Ni Putu Rediatni Giri (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2022)
This research aims to find out whether the period of time, guarantees, interest rates and character affect the occurrence of bad loans in lpd Pakraman Sanur village, South Denpasar subdistrict. Sanur Village Credit Institution is a financial institution established by the customary village or sanur village and serves as an economic support and wealth of indigenous villages that carry out the function of improving the economy of the village community. One of lpd's activities in sustaining the community economy is the provision of credit that provides money lending. But in this credit grant of course there is a risk in the form of bad credit. The emergence of bad credit is due to several factors that make the credit return process hampered. The data collection methods in the study used questionnaires and interviews. The population in this study was bad loan customers in the period 2015-2019 as many as 68 people. Sampling is done by saturated sampling method that uses all members of the population as a sample, so the sample in this study is bad credit customers in the period 2015-2019 at LPD Pakraman Sanur Village, South Denpasar Subdistrict, while the analysis technique uses classical analysis test, multiple linear regression analysis, determination coefficient analysis, F-test test results and test results t. The results showed that variables in the term, guarantee, and character of debtors negatively affect bad loans, while variable interest rates have a positive effect on bad loans.